Evidence-based policymaking: A review - Strydom, Wilma F. (Academy of Science of South Africa, 2018)
The process of facilitating the uptake of evidence, for example, scientific research findings, into the policymaking process is multifaceted and thus complex. It is therefore important for scientists to understand this process in order to influence it more effectively. Similarly, policymakers need to understand the complexities of the scientific process to improve their interaction with the scientific sphere. This literature review addresses those factors that influence the uptake of scientific evidence into policymaking, the barriers to using science in policymaking, as well as recommendations for improved science–policymaking interaction. A visual diagram of the gears of a car is used to convey the message of the complexities around the engagement between science and policymaking. It is concluded that the issue of evidence-based policymaking remains unresolved and questions for future research on the science–policy interface are raised.